Ministry Of Industry And Foreign Trade Decree No. 371 of the year 2013 = وزارة الصناعة والتجارة الخارجية قرار رقم 371 لسنة 2013 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.